2006
DOI: 10.1074/jbc.m601314200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Binding Properties of the CD2 and CD244 (2B4)-binding Protein, CD48

Abstract: The structural analysis of surface proteins belonging to the CD2 subset of the immunoglobulin superfamily has yielded important insights into transient cellular interactions. In mice and rats, CD2 and CD244 (2B4), which are expressed predominantly on T cells and natural killer cells, respectively, bind the same, broadly expressed ligand, CD48. Structures of CD2 and CD244 have been solved previously, and we now present the structure of the receptor-binding domain of rat CD48. The receptor-binding surface of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…This led to the identification of amino acid residues comprising the Ln511/521-binding site on Lu gp. An unexpected finding is that, unlike most cell-cell interactions that characteristically result from the formation of cell adhesion pairs between the membrane-distal domains of cell adhesion molecules (eg, CD2:CD58 26 and CD2: CD48 27 ), Lu gp uses a more membrane-proximal interdomain junction region to form a critical part of its Ln-binding site.…”
Section: Introductionmentioning
confidence: 94%
“…This led to the identification of amino acid residues comprising the Ln511/521-binding site on Lu gp. An unexpected finding is that, unlike most cell-cell interactions that characteristically result from the formation of cell adhesion pairs between the membrane-distal domains of cell adhesion molecules (eg, CD2:CD58 26 and CD2: CD48 27 ), Lu gp uses a more membrane-proximal interdomain junction region to form a critical part of its Ln-binding site.…”
Section: Introductionmentioning
confidence: 94%
“…CD2 associates with the Src family tyrosine kinases Lck and Fyn and through these kinases couples to downstream signal transduction pathways (18 -20). Proline-rich sequences of the cytoplasmic domain of CD2 have been shown to be involved in the interaction with the Src homology 3 (SH3) 4 domains of these kinases (20 -22), also with the SH3 domain of the adaptor protein CD2AP (23), connecting CD2 to the cytoskeleton, and additionally with the SH3 domain of CD2BP1 (24), resulting in the down-regulation of activation-dependent CD2 adhesion. CD2 binds to the GYF domain of CD2BP2 as well, an interaction resulting in cytokine production (25).…”
mentioning
confidence: 99%
“…The extracellular domain of CD2 is composed by two Ig superfamily domains (2), of which the membrane-distal V-like domain is involved in the binding to the ligand (3). CD2 has different ligands in rodents (CD48) and humans (CD58), and the mechanisms of ligand binding are substantially different, as assessed by thermodynamic analysis (4,5). Nevertheless, engagement of CD2 to CD58 in humans, or to CD48 in rodents, facilitates adhesion between T cells and APC and is proposed to promote the formation of an optimal intercellular membrane spacing (ϳ140 Å) suitable for TCR recognition of a peptide Ag bound to MHC (6).…”
mentioning
confidence: 99%
“…The resulting interaction between CD6 and CD166 is therefore unusual, because most other T cell surface proteins mediating cell-cell interactions bind through their N-terminal domains. However, affinity and kinetic measurements revealed that, in solution, binding occurs with a K d of 0.4 -1.0 M (14), relatively strong compared with most other leukocyte adhesion pairs, albeit in the range of low-affinity interactions characteristic of cell surface receptors (25)(26)(27).…”
mentioning
confidence: 99%